Properties of Emerging Organizations - Katz, Jerome A.; Gartner, William B. (Academy of Management Review, 1988)
This article explores the characteristics of emerging organizations and suggests that emerging organizations can be identified by four properties: intentionality, resources, boundary, and exchange. These properties are defined and discussed. Suggestions are made for selecting samples for research on emerging organizations. Implications for research and theory on new and emerging organizations are discussed.